Relative elimination of paralytic shellfish poisoning (PSP) toxins and escherichia coli cells from perna viridis depurated using an ultraviolet-assisted purification system - Cabagnot, Riva Jena Leyva; Azanza, Ma. Patricia V. (2000)
ABSTRACT Ultraviolet-assisted depuration system was used to detoxify field-contaminated Perna viridis harvested between March 1999 to August 1999 from commercial shell stock culture sites in Zambales, Philippines. The changes in the paralytic shellfish poisoning (PSP) toxin and microbial content of purified mussels were monitored. The depuration was done for 72 h in seawater with salinity and temperature of 31-35 ppt and 20-25°C, respectively. A 25.58% maximum reduction of PSP toxicity from whole mussel meat was achieved during the 72h depuration period. The rank order of PSP toxin elimination from depurated green mussel soft tissue was: digestive system and gonads> adductor muscle> foot> gills and mantles. The depuration process effected bacterial eliminations of >99% and >89% for TPC and Escherichia coli counts of whole mussel meat, respectively. Reductions of about 91% for TPC and 96% for E. coli counts were recorded in the depuration water.
Thesis (BSFT)--University of the Philippines, Diliman
Keywords: Poisonous shellfish